RUMAH INDONESIA BERNUANSA âINDONESIA NEGARA 1000 BUDAYAâ SEBAGAI SARANA INFORMASI SEKALIGUS UNTUK MEMPERKENALKAN BUDAYA INDONESIA PADA MASYARAKAT DI PERBATASAN - Falah, Muhammad Wasal; N., Nasrudin; Jayanti, Yeni; Utami, Sutri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Indonesia is a country that has an abundance of different cultures. With the abundance of culture possessed, Indonesia should be able to preserve it. However, in reality some Indonesian culture has been claimed by neighboring countries such as Reog Ponorogo is claimed by Malaysia, and others. So must to do an action that can minimize the threat. One solution is by the Rumah Indonesia. Rumah Indonesia is a public facility that concept